Decision making and its relationship to the mature personality of university students (Journal of the College of Basic Education, 2022)
The current research seeks to achieve a number of goals, including measuring decision-making and mature personality among students of the University of Baghdad, as well as knowing the significance of the differences between the two variables among university students according to the gender variable, in addition to knowing the nature of the correlations between the two variables. (The mature personality scale) The scientific conditions used in the preparation of the psychological scales were taken into account in the preparation of the two scales